Health care services to adolescents in six cities of the 12nd regional health coordination - Luciana Griebeler Oliveira; Zaleia Prado de Brum; Stefanie Griebeler Oliveira; Simone Wünsch; Raquel Pötter Garcia; Bruna Sodré Simon; Dyan Jamilles Teixeira Brum (Universidade Federal de Santa Maria, 2011)
This study aimed to know the offer of services of health care to adolescents in the cities of the 12nd Regional Health CoordInation (RHC), through the perception of nurses and tutelary counselors. It is a qualitaive research. The sample was constituted by tutelary counselors and nurses of six, out of 25 cities of the 12nd RHC of Rio Grande do Sul. Data was collected through semi-structured interviews and then organized to proceed to content analysis, which was later carried out. After such stage, two categories emerged: Offer of Services to Adolescents and Offer of Services to Adolescents in Social Vulnerability. Several actions are directed to adolescents, as concerns the health, educational, religious or social fields. However, in most of the cities such actions are not articulated. Specific actions towards adolescents in social vulnerability were highlighted